On the identity of the rubiaceous Timonius quadrasii (Guettardeae: Cinchonoideae): its typification and transfer to Rothmannia (Gardenieae: Ixoroideae). Issue 2 (3rd July 2017) - Chavez, Jayson G.; Liede-Schumann, Sigrid; Meve, Ulrich
Abstract: The Philippine endemic Timonius quadrasii Elmer exhibits disparate features against the current delimitation of Timonius, and of the subfamily Cinchonoideae. Morphological examination revealed very short axillary branchlets (brachyblasts) bearing a single leaf creating a 3 : 3 nodal pattern, pseudo-axillary inflorescences and left-contorted corollas, which fits to the delimitation of Rothmannia from the subfamily Ixoroideae. In the present work, T. quadrasii is lectotypfied and the new combination Rothmannia quadrasii (Elmer) J.G. Chavez, Liede & Meve is proposed.